Internal Factors that Associated with Difficulty Nursing Academy Student Learning Syekh Yusuf Gowa - Nurhijrani Nurhijrani (Sean Institute, 2021)
learning difficulties at the Syekh Yusuf Gowa Nursing Academy. The research design used is cross-sectional. Samples were taken from students who had difficulty learning the techniques of purposive sampling. The sample size is 63 students, consisting of 25 level III students and 38 level II students. The instruments used for data collection were questionnaires and documentation of the results of the evaluation of even-semester student learning for the 2020–2021 period. The data that has been collected is processed using the SPSS program. Data processing uses statistical tests such as Chi-Square with a significant level a < 0.05. The results of data processing show that there is a relationship between learning motivation and learning difficulties (p = 0.001), a relationship between study habits and learning difficulties (p = = 0.438). The conclusion of this study is that there is a relationship between learning motivation factors, study habits, lecturer methods, and supporting facilities and tools and student learning difficulties at the Sheikh Yusuf Gowa Nursing Academy. So that the motivation and study habits of students can be improved to overcome these learning difficulties, one way to conduct tutoring for students.